Identification of Differentially Expressed Genes and Pathways Involved in Growth and Development of Mesona chinensis Benth Under Red- and Blue-Light Conditions - Tang, Danfeng; Huang, Qinfen; Wei, Kunhua; Yang, Xiaonan; Wei, Fan; Miao, Jianhua (Frontiers in Plant Science, 2021)
Mesona chinensis Benth (MCB) is an important Chinese herbal medicine. The plant factories might be one of the ways to solve the shortage of MCB supply. In this study, the MCB seedlings were treated under red (R) and blue (B) light in the plant factory. Results show that red light promoted the growth and development of MCB in comparison with blue light. Under the red light condition, the biomass, plant height, and root characteristics were significantly higher than those of blue light, while the SPAD of red light treatment was significantly lower than that of blue light. Red light also significantly promoted the content of soluble sugar and pectin of MCB compared with blue light. Transcriptome analysis showed that a total of 4165 differentially expressed genes (DEGs) were detected including 2034 up-regulated and 2131 down-regulated. Of these, 1112 DEGs including 410 up-regulated and 702 down-regulated genes were associated with 111 pathways. Moreover, a total of 8723 differentially expressed transcription factors (TFs) were identified in R vs B and these TFs were distributed in 56 gene families. Metabonomic results revealed that a total of 184 metabolites and 99 differentially expressed metabolites (DEMs) (42 up-regulation and 57 down-regulation) were identified in red and blue light treatments. Integrative analysis of transcriptome and metabolome unveiled that a total of 24 pathways included 70 compounds (metabolites) and were associated with 28 unigenes. In particular, these pathways included starch and sucrose metabolism, phenylpropanoid biosynthesis, cysteine and methionine metabolism, glycolysis/gluconeogenesis, and pentose and glucuronate inter-conversions, etc. The unigenes included asparagine synthetase (AS), thymidine kinase (TK), alpha, alpha-trehalose-phosphate synthase (TPS), phosphatase IMPL1 (IMPL1), dihydroflavonol 4-reductase (D4R), and 4-coumarate-CoA ligase-like 6 (4CL6), bifunctional aspartokinase/homoserine dehydrogenase 1 (thrA), and abscisic acid 8' -hydroxylase 2 isoform X1 (ABA8). It was indicated that these pathways and genes might play important roles in the growth and development of MCB. The current study laid a foundation for the future research of MCB.